2000
DOI: 10.1002/etc.5620190112
|View full text |Cite
|
Sign up to set email alerts
|

Intra‐ and intertreatment variability in reference toxicant tests: Implications for whole effluent toxicity testing programs

Abstract: Abstract-Whole effluent toxicity tests are used in permitting programs across the United States to determine whether effluents are potentially toxic to aquatic biota in receiving environments. In cases where whole effluent toxicity tests indicate unacceptable toxicity, corrective measures or further testing (e.g., field tests) may be required. To be consistent and fair to permit holders, whole effluent toxicity test outcomes (e.g., pass or fail) should not be strongly influenced by intra-and interlaboratory va… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
12
0

Year Published

2002
2002
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(14 citation statements)
references
References 12 publications
2
12
0
Order By: Relevance
“…Calculating the CV allows one to relate the variation observed for one chemical to that of another. In this study, these values were always <20 for both 3C2B and MC, well within the acceptable range for aquatic toxicity tests as CV values were below the upper limit of 40 for intra-laboratory variability (Moore et al 2000; Hagen et al 2009, Piazza et al 2012). Previous studies with this system have reported CVs for the EC 50 similar to those obtained herein (Dawson et al 2014b, 2016).…”
Section: Discussionsupporting
confidence: 75%
“…Calculating the CV allows one to relate the variation observed for one chemical to that of another. In this study, these values were always <20 for both 3C2B and MC, well within the acceptable range for aquatic toxicity tests as CV values were below the upper limit of 40 for intra-laboratory variability (Moore et al 2000; Hagen et al 2009, Piazza et al 2012). Previous studies with this system have reported CVs for the EC 50 similar to those obtained herein (Dawson et al 2014b, 2016).…”
Section: Discussionsupporting
confidence: 75%
“…Other investigations based on Biolog plates come to a comparable coefficient of variation for different soil nutrient amendments (42% in a laboratory experiment with sulfachloropyridazine [27] or 16‐55% at different field sites that were not contaminated with metals [12]). Overall, the variation is in the range as observed for intralaboratory variation in other complex ecotoxicological test systems [28,29]. Although a coefficient of variation of smaller than 30% is generally aimed at, this criterion is frequently exceeded in test systems with difficult environmental media such as soil, with difficult polar and degrading test substances, and with non‐standardized communities in place of single standardized test species.…”
Section: Discussionmentioning
confidence: 99%
“…The CVs for each sample were lower than those calculated in the original standard volume A. abdita round‐robin from Schlekat et al [19] (Table 6). Interlaboratory variability can arise because of differing source organisms, laboratory conditions, and analyst experience [25]. Detailed protocols were used in this study and Schlekat et al [19].…”
Section: Discussionmentioning
confidence: 99%